Predicting Depression among Shiraz University Students Based on Patience and its Components - Mansooreh Mahdiyar; Seyed Mohammad Reza Taghavi; Mohammad Ali Goudarzi (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: Given the prevalence of depression in different societies, identifying its predictive factors with the purpose of prevention and early intervention is of great importance. In Islam, emphasis has been put on patience as a determining factor in preventing depression. The aim of this study was to predict depression based on patience and its components. Method: This study adopted a correlational method. The population included Shiraz University students, from whom 209 were selected through convenience sampling. Research instruments were Patience Scale and Beck Depression Π Inventory. In order to analyze the data, stepwise and enter regression were used. In this study, all the ethical issues were considered; besides, the authors declare no conflict of interest. Results: The results showed that persistence and contentment can predict depression both significantly and negatively. Moreover, the total score of patience could also predict depression significantly and negatively. Conclusion: Regarding the role of this religious variable in developing and prevention of depression, therapists and researchers should pay more attention to patience and its components. For downloading the full-text of this article please click here.